Late Precambrian glaciogenic sedimentary rocks in southern Africa: a compilation with definitions and correlations - A. Kröner; K. Rankama (Bulletin of the Geological Society of Finland, 1973)
Evidence of ancient glaciations is summarized, and the terminology dealing with glaciogenic and nonglaciogenic sedimentary rocks is discussed. The term tillite is used as a comprehensive genetic term for both continentally deposited and ice-rafted indurated tills. The glaciogenic origin of any rock called tillite must have been proved beyond doubt. The term mixtite is used for sedimentary rocks that resemble tillites but are of uncertain or unknown origin. A comprehensive compilation of all known Late Precambrian glaciogenic sedimentary rocks in South Africa and in South West Africa is presented. These rocks seem to form two distinct groups that may indicate the existence of two periods of glaciation. Glaciogenic rocks in other countries in Africa occupy similar stratigraphic positions. This evidence strengthens the possibility of the existence of a severe continentwide Late Precambrian glaciation in Africa. Comments on the Late Precambrian glaciation in Australia and in South America are given.